The process of digitalization of economy in Armenia in the scope of State Strategy - Asryan, Karine (Bulletin of Yerevan University G: Economics, 2023)
In recent years the process of performance of any country in internal and external markets, as well as development in economic and other sectors, including security issues, the major role plays the application of information technologies (IT). The information technologies and the digitalization process in modern world plays strategic role for every country, including Armenia, because it creates the preconditions for optimal development of internal operating system within the country and its integration with other countries with the aim of co-operation in different spheres. Therefore, taking into account the tendencies of digitalization of economy, provision of measures of conformity with international standards is very important for raising the competitiveness and security of country. Based on this, the priority for any country is development of IT operations in internal and external environment. Specific significance in this context acquires the necessity of digitalization of different processes and operations in economic and business sector, state governance and public services. For that purpose, in scope of necessary measures stated in this article by author, are the following: a. to strengthen the cybersecurity measures in digital economy building operations in order to provide secure data transfer protocols, to create the systems of corelating cyberenvironment, and confidentiality measures. Logically, the main coordinator and responsible for all this process should be The Ministry of HighTech Industry of RA with the provision of correlated financial, technological, human and other necessary resources. b. it is vital to provide the corresponding trainings and explanative work within the society and governmental structures in order to digitalize and make more transparent the activity of importing and exporting business units, which play significant role in GDP and state revenues.
Keywords: Strategy of digitalization; information technologies; digitalization of economy; digital business; cybersecurity; electronic services; e-governance